The war of civilizations in the works of Armenian artists - Vardanyan, Hripsime (History and Culture, 2023)
Even in ancient civilizations, battle scenes were created in different branches of art: sculpture, relief, mural painting, etc. In ancient civilizations, they served not only as a model of art, but, perhaps, rather as a means of preaching. By depicting their leaders as the victors (who may have, actually, lost the war) of the state, the government aimed atupholding the spirit of the warrior, the victor. The art at all times has been a direct reflection of historical events, thereby creating a platform for researchers to uncover the events of the given period centuries and millennia later. Therefore, the history of art is first of all the history of humanity, the history of civilizations. In this article we will present the works in Armenian art of XIX-XXI centuries (paintings and graphics) concerning the war and civilizational situations and conditioned by them, making comparisons not only with Armenian but also with world art samples. The depictions of Armenian artists include the reflection of our heroic pages, as well as the painful pages of our history, starting with the depiction of widespread massacres and inconceivable atrocities that began in various regions of Western Armenia in the 1890s, until the events of Sumgait. The antiquity of all this does not at all heal the wounds, leading to oblivion, moreover, it is the basis of new creations for artists to prevent human and cultural genocide, civilizational wars.